High-efficiency bidirectional resonant WPT system for electric vehicles - Marojahan Tampubolon; Huang-Jen Chiu; Hsin-Che Hsieh; Jing-Yuan Lin; Yao-Ching Hsieh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The wireless power transfer (WPT) system has become popular given its safety and flexibility in electric vehicle (EVs) charging applications. Due to the increasing number of EVs, vehicle to grid (V2G) can be implemented in the future in which a bidirectional WPT is one of the key features. A high-efficiency bidirectional resonant WPT system is studied and implemented in this study. Besides bidirectional capability, single stage and regulated output voltage are other features of this work. It is done by using the variable frequency control without sacrificing efficiency and conforming to the typical frequency range of the WPT system for EVs application. The analysis of the series-series compensated WPT is presented, followed by the design consideration of the developed bidirectional WPT system. At last, the implementation and experimental results for a 3 kW laboratory prototype are also presented to show the validity and the feasibility of the proposed scheme. A 96.8% efficiency at a 210-mm gap and a 95% efficiency at a 250-mm gap can be achieved under a rated power condition.